Analysis the advanced ICT usage of the Hungarian SME sector for preparing a domestic agri-food research - Botos, Szilvia; Felföldi, János; Várallyai, László; Péntek, Ádám; Szilágyi, Róbert (Applied Studies in Agribusiness and Commerce, 2017)
In the Hungarian agro-food sector SMEs have a key role but regarding the tendency of the performance of SME sector, comparing to EU-28 average, the performance of Hungarian SME sector has gradually worsened between 2008 and 2015 while the EU average has an increasing trend. ICT can help enterprises and this article is an overview of the ICT situation of Hungarian SMEs. It is important to analyse in detail the ICT usage characteristics of agro SMEs in the food supply chain because these ICT devices, tools and services are crucial to smooth the information flow within the chain. For all these reasons our work aims to find out how Hungarian agro-food SMEs use ICT and how ICT adoption affect their business procedures, performance and development. A striking observation to emerge from the data comparison is the difference among SMEs and large enterprises regarding the usage of the different basic and advanced ICT solutions. A much bigger percent of large companies use advanced ICT then SMEs and mainly small enterprises are lagging behind as the attitudes of medium sized enterprises are rather similar to the large ones. In Hungary small enterprises in agro-food industry are in difficult financial state and for them free Cloud Computing services can offer good opportunities as they do not have initial costs. ICT adoption is very important to them as ICT sector is a dynamically growing sector and if customers and partners of an enterprise adapt faster to these technological innovations, it may have a negative effect on the different processes, performance and financial results of the organisation. In this article our aim was to determine the main question groups for our questionnaire which focus mainly on ICT solutions supporting the quality of communication and relationship between partners. As the basic IT tools are available in the major part even in the SMEs besides large companies, the two main issues will be the usage of advanced online services and the usage of high quality ICT solutions.JEL Code: M15